Restoran Khas Melayu Riau Di Pekanbaru Dengan Pendekatan Arsitektur Hijau - Ogie Pratama; Pedia Aldy; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is one of the developing city, economic growth in Pekanbaru gave the influence on business development especially restaurant. The restauran not only has the function of eating and drinking, but also as a means of entertaiment and recreation. See the more rapid development of globalization, local culture increasingly closed and was squeesed, as well as the lack of space for local culure stay afloat. Then by applaying the concept of “Green And Culture” in buildings it will be a place to back lifting the local culture. And then in the design of Riau malay restaurant created a pattern of mass order which followed the application the concept of culture so a pattern of mass order have characterized from Riau Malay motif. The design also applies the principles of green architecture, the principle of GBCI becomes a reference to meet green architecture approach that became the method in the design of Riau malay restaurant with an area of 3 ha.Keywords: Restaurant, Green Architecture, Culture, Riau Malay, GBCI.